Rescuing Trafficking Mutants of the ATP-binding Cassette Protein, ABCA4, with Small Molecule Correctors as a Treatment for Stargardt Eye Disease - Sabirzhanova, Inna (J Biol Chem, 2015)
Stargardt disease is the most common form of early onset macular degeneration. Mutations in ABCA4, a member of the ATP-binding cassette (ABC) family, are associated with Stargardt disease. Here, we have examined two disease-causing mutations in the NBD1 region of ABCA4, R1108C, and R1129C, which occur within regions of high similarity with CFTR, another ABC transporter gene, which is associated with cystic fibrosis. We show that R1108C and R1129C are both temperature-sensitive processing mutants that engage the cellular quality control mechanism and show a strong interaction with the chaperone Hsp 27. Both mutant proteins also interact with HDCAC6 and are degraded in the aggresome. We also demonstrate that novel corrector compounds that are being tested as treatment for cystic fibrosis, such as VX-809, can rescue the processing of the ABCA4 mutants, particularly their expression at the cell surface, and can reduce their binding to HDAC6. Thus, our data suggest that VX-809 can potentially be developed as a new therapy for Stargardt disease, for which there is currently no treatment.